Aligning Grade V Arabic Writing Tasks with Brown’s Principles: A Content Analysis of the Kementerian Agama Textbook - Naura Nadhifah; My Love Faizah Putri; Abul Ma'ali; Ardelia Nabila Hermayana (Fakultas Tarbiyah dan Keguruan, 2026)
Purpose – This study examines the extent to which the Grade V Arabic textbook issued by the Kementerian Agama Republik Indonesia supports writing instruction in accordance with the pedagogical principles of Douglas Brown. Design/methods/approach – The research used a qualitative content-analysis method to scrutinize maharah al-kitābah items in the Grade V textbook intended for Madrasah Ibtidaiyah students and to map task types against a theoretical coding framework. Findings – Analysis identified predominant task formats—picture-based word and phrase writing, simple sentence assembly, and constrained dialogue completion—that systematically reinforce vocabulary and orthographic accuracy. Evidence of Brown’s principles (e.g., meaningful learning, affective support, and strategic investment) appears in the textbook’s design, yet explicit process-writing sequences (prewriting, drafting, revising, publishing) and opportunities for extended, genre-varied composition are largely absent. Research Implications – These patterns suggest that the textbook affords essential foundational skills but insufficiently scaffolds fluency, idea development, and iterative revision for young L2 writers. The study recommends integrating concise, age-appropriate process-writing modules, teacher-facing scaffolds, and pilot classroom trials paired with professional development to evaluate impacts on composition outcomes. Limitations include single-textbook scope and analysis limited to printed materials rather than classroom enactment, which future mixed-methods research should address.